A study of translation techniques in the book of “Banal Aesthetics & Critical Spiritualism” by Erik Prasetya and Ayu Utami - Juhana, Juhana; Efendi, Yudi; Ardiasih, Lidwina Sri (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2018)
The present study was aimed at describing the translation techniques used by the translator in the books of Banal Aesthetics Critical Spiritualism written by Erik Prasetya Ayu Utami. Descriptive qualitative approach was employed through collecting the data related to the concerned and researched problems. The theory of translation technique suggested by Molina and Albir became the reference to classify the translation techniques used in the translation of the books of Banal Aesthetics Critical Spiritualism. Document analysis and literature review were employed to collect the data. The analysis results indicated that there were 15 types of translation techniques used from 18 ones as what is suggested by Molina and Albir. The five most widely used techniques of translation techniques in the books of Banal Aesthetics Critical Spiritualism were: literal translation (33, 46%), modulation (14.96%), reduction (14.56%), established equivalent (11.02%), and borrowing (9.84%). Meanwhile, three translation techniques that were not used are: calque, substitution, and variation.